Estudio de estrategias de administración de recursos de radio en un sistema 3g. - Balseca Del Campo, David Benjamín (2010)
Nowadays guaranteeing the quality of service of users of a celular network it’s more challenging each time due to the increase of the number of aplications and services that are appearing with the development of new technologies, this is why it is necessary to manage the radio resources in an efficient way. By using radio resource management strategies it is possible to minimize the congestion problems caused by excesive users interference as well as the problems caused by near-far effect. In this paper we present four strategies related to radio resource management specifically: Congestion Control, Admission Control, Handover and Power Control, besides we will show the results obtained after simulating two power control algorithms using MatLab and we will evaluate their efficiency after being submitted to different scenarios of different numbers of mobiles.